2022
DOI: 10.1111/jch.14590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catheter‐based renal denervation on renin‐aldosterone system, catecholamines, and electrolytes: A systematic review and meta‐analysis

Abstract: In recent years, catheter-based renal denervation (RDN) has emerged as a promising instrumental therapy for hypertension. The interruption of sympathetic nervous system was regarded as a possible mechanism for RDN regulating blood pressure.While the results reflected by renin-angiotensin-aldosterone system (RAAS), catecholamines and electrolytes remained inconsistent and was never systematically assessed. Pubmed, Embase, and Web of Science were comprehensively searched from inception to September 5, 2021. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Identifying likely responders in advance may improve the cost-effectiveness of the procedure. RDN has been demonstrated in previous research to reduce renin levels [ 17 19 ], and our team's studies indicate that hypertensive patients with high renin levels have better treatment outcomes when taking RDN [ 20 ]. As a result of this 10-year follow-up study, it has also been confirmed that RDN is more effective at lowering BP in hypertensive patients with a high renin level, providing strong evidence for the selection of RDN indications in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Identifying likely responders in advance may improve the cost-effectiveness of the procedure. RDN has been demonstrated in previous research to reduce renin levels [ 17 19 ], and our team's studies indicate that hypertensive patients with high renin levels have better treatment outcomes when taking RDN [ 20 ]. As a result of this 10-year follow-up study, it has also been confirmed that RDN is more effective at lowering BP in hypertensive patients with a high renin level, providing strong evidence for the selection of RDN indications in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Mahfoud F et al showed that RDN could inhibit renin secretion [3] . A newly published meta-analysis revealed that plasma renin activity was considerably decreased following RDN, while plasma aldosterone, norepinephrine, serum and urinary electrolytes exhibited no signi cant changes [4] .Therefore, theoretically, RDN may not be suitable for the treatment of primary aldosteronism. Just like Schiavone D said that unilateral laparoscopic adrenalectomy remains the gold standard for the treatment of patients with AVS-proven unilateral APA.…”
Section: Discussionmentioning
confidence: 99%
“…O sistema renina-angiotensina-aldosterona é chave central na regulação da pressão arterial. A DSR, ao interromper a via simpática, reduziu a atividade de renina plasmática e os níveis de noradrenalina tecidual renal em modelos animais (86) e de atividade de renina plasmática e aldosterona sérica em subestudo do SPYRAL HTN OFF MED (87), ambos sem a interferência de anti-hipertensivos, embora metanálise recentemente publicada evidencie que a aldosterona plasmática não se alterou significativamente após DSR (88).…”
Section: Discussionunclassified